Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/infdis/jiu020
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Immunity and Influenza

Abstract: Sex-specific endocrine and immune responses are widely recognized to account for differential disease outcomes between females and males. Surprisingly, sex-specific risk assessments for influenza, a viral pathogen that affects human populations worldwide through seasonal epidemics and irregular occurring pandemics, are sparse and-if available-ambiguous. To date, this precludes proposing an unequivocal sex-dependent susceptibility to influenza. However, one undisputable observation recurrently confirmed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 30 publications
7
77
0
1
Order By: Relevance
“…By randomly assigning participants to three delivery methods, we increased our confidence that the acceptability of the method is not limited to a specific delivery approach. Our focus on pregnant women also adds to the value of our pilot, as innovative community‐based methods are especially needed to address many unanswered questions about the epidemiology of influenza and vaccine effectiveness among pregnant women …”
Section: Discussionmentioning
confidence: 99%
“…By randomly assigning participants to three delivery methods, we increased our confidence that the acceptability of the method is not limited to a specific delivery approach. Our focus on pregnant women also adds to the value of our pilot, as innovative community‐based methods are especially needed to address many unanswered questions about the epidemiology of influenza and vaccine effectiveness among pregnant women …”
Section: Discussionmentioning
confidence: 99%
“…The existence of gender bias in the immune response to infectious diseases is further supported by numerous in vivo studies focused on Mycobacterium marinum [10], Streptococcus pneumoniae [11], Streptococcus pyogenus [12], Plasmodium chabaudi [13], and Mycoplasma pulmonis [14]. A similar tendency has been seen in humans against numerous pathogens including: Mycobacterium tuberculosis [15], Influenza virus [16] and community-acquired pneumonia [17] in which men are more susceptible than women.…”
Section: Introductionmentioning
confidence: 91%
“…A strong sex bias is observed for many autoimmune diseases(2), which are much more common in females, including autoimmune thyroid diseases, systemic sclerosis, systemic lupus erythematosus. Furthermore, the incidence and severity of several microbial infections, including malaria and tuberculosis(3), influenza(4), hepatitis(5) and HIV-1(6) are different between the sexes(7). In HIV-1 infection, clinical studies have shown faster disease progression and stronger immune activation in females compared to males for the same level of viral replication, as well as better control of initial viremia in women during primary infection.…”
Section: Introductionmentioning
confidence: 99%